Integral use of sugarcane vinasse for biomass production of actinobacteria: Potential application in soil remediation - Aparicio, Juan Daniel (2017)
The use of living actinobacteria biomass to clean up contaminated soils is an attractive biotechnology approach. However, biomass generation from cheap feedstock is the first step to ensure process sustainability. The present work reports the ability of four actinobacteria, Streptomyces sp. M7, MC1, A5, and Amycolatopsis tucumanensis, to generate biomass from sugarcane vinasse. Optimal vinasse concentration to obtain the required biomass (more than 0.4 g L−1) was 20% for all strains, either grown individually or as mixed cultures. However, the biomass fraction recovered from first vinasse was discarded as it retained trace metals present in the effluent. Fractions recovered from three consecutive cycles of vinasse re-use obtained by mixing equal amounts of biomass from single cultures or produced as a mixed culture were evaluated to clean up contaminated soil with lindane and chromium. In all cases, the decrease in pesticide was about 50% after 14 d of incubation. However, chromium removal was statistically different depending on the preparation methodology of the inoculum. While the combined actinobacteria biomass recovered from their respective single cultures removed about 85% of the chromium, the mixed culture biomass removed more than 95%. At the end of the reused vinasse cycle, the mixed culture removed more than 70% of the biological oxygen demand suggesting a proportional reduction in the effluent toxicity. These results represent the first integral approach to address a problematic of multiple contaminations, concerning pesticides, heavy metals and a regionally important effluent like vinasse.